1998
DOI: 10.7164/antibiotics.51.235
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Cytotoxicity of Asterriquinone Derivatives.

Abstract: The antitumor agent, asterriquinone (ARQ) is a known metabolite isolated from the mycelium of Aspergillus terreus IFO 61231). YAMAMOTO et al. reported that ARQ analogues having a 2, 5-dimethoxy-p-benzoquinone moiety (ARQ dimethyl ether: ARQDMe)2,3) and the 2, 5-diamino-p-benzoquinone moiety (diamino ARQ: ARQDA)4) did not show any Cytotoxicity. As reported in our previous communication5), a new metabolite, asterridinone, which has a furo [3, 2-b] furan moiety instead of the p-benzoquinone moiety of ARQ, did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…For example, asterriquinone A1 ( Fig. 1), has been shown to arrest the cell cycle in G 1 and promote apoptotic cell death [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, asterriquinone A1 ( Fig. 1), has been shown to arrest the cell cycle in G 1 and promote apoptotic cell death [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…(De Guzman et al, 1994;Fredenhagen et al, 1997;Mocek et al, 1996;Ooike et al, 1997;Sekita, 1983). The asterriquinones and related bis-indolyl-quinones have been studied as potential antitumor agents because of their DNA-intercalating properties (Kaji et al, 1998;Yamamoto et al, 1976). Some of them are also HIV-l protease inhibitors (Fredenhagen et al, 1997), antibacterial, and toxic to insects (De Guzman et al, 1994).…”
Section: Lead Identification and Isolationmentioning
confidence: 99%
“…Since then several benzoquinones, such as asterriquinones [81][82][83][84] (76)(77)(78)(79)(80)(81)(82)(83)(84), isocochliodinol (85), semicochliodinols (86, 87) [89], and terphenylquinones (88)(89)(90)(91)(92), were isolated [90][91][92]. Although asterriquinones were well recognized for their antibiotic and antitumour activity [87], it took around 25 years to realize their kinase inhibitory potential [85,86,88]. The bioactivity profiling of these derivatives clearly showed that the presence of the 2,5 dihydroxy groups and which of either an indol or a phenol on 3 and 6 positions, in the benzoquinone, is necessary for bioactivity.…”
Section: Benzoquinones (Table 83)mentioning
confidence: 99%